Are there any risks to taking creatine as a supplement?. Issue 1 (January 2015) - Grasso‐Knight, Guido
Abstract : Evidence‐Based Answer : Yes, taking creatine monohydrate is associated with decreased activities of daily living in patients with McArdle disease (SOR: B, small RCT) and increased edema in patients with amyotrophic lateral sclerosis (ALS); there does not appear to be any effect on renal function in patients with ALS or diabetes (SOR: B, small RCTs). In athletes, creatine may be associated with fluid gain, gastrointestinal upset, and muscle cramps, with safety unknown during long‐term use (SOR: C, consensus opinion).